De l’expérience à l’existence. Le goŭt, le social, le modal - Boutaud, Jean-Jacques (E|C, 2020)
Without offering an overview, pretentious and risky, on these semiotic practices, it will be a question of taking up here a few moments and therefore some diagrams of the semiotic construction on taste. See how they made it possible to move from the ontological and phenomenological complexity of taste sensation and perception to a logical framework on the processes of signification at play, while dealing with this depth plane.